Analisis Perhitungan Jembatan Gelagar I pada Jembatan Jalan Raya dan Jembatan Kereta Api - Irpan Hidayat (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The bridge is a means of connecting roads which is disconnected by barriers of the river, valley, sea, road or railway. Classified by functionality, bridges can be divided into highway bridge and railroad bridge. This study discusses whether the use of I-girder with 210 m height can be used on highway bridges and railway bridges. A comparison is done on the analysis of bridge structure calculation of 50 m spans and loads used in both the function of the bridge. For highway bridge, loads are grouped into three, which are self weight girder, additional dead load and live load. The additional dead loads for highway bridge are plate, deck slab, asphalt, and the diaphragm, while for the live load is load D which consists of a Uniform Distributed Load (UDL) and Knife Edge Load (KEL) based on "Pembebanan Untuk Jembatan RSNI T-02-2005". The load grouping for railway bridge equals to highway bridge. The analysis on the railway bridges does not use asphalt, and is replaced with a load of ballast on the track and the additional dead load. Live load on the structure of the railway bridge is the load based on Rencana Muatan 1921 (RM.1921). From the calculation of the I-girder bridge spans 50 m and girder height 210 cm for railway bridge, the stress on the lower beam is over the limit stress allowed. These results identified that the I-girder height 210 cm at the railway bridge has not been able to resist the loads on the railway bridge.